2019
DOI: 10.1016/j.physbeh.2017.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in nicotine intravenous self-administration: A meta-analytic review

Abstract: Overall, the results revealed that female rats display higher levels of nicotine IVSA than males, suggesting that the strong reinforcing effects of nicotine promote tobacco use in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…When it comes to gender study, Travis et al observed the susceptibility of lung cancer in female smokers because of tar exposure compared to male counterparts [21]. Similarly, our study also suggests that female smokers are more prone in developing cognitive decline compared to male smokers which may be due to the fast rate of nicotine metabolism by the female hormones and its effect on the cognitive decline [22]. Additionally, females exhibited a higher amount of nicotine intake and the total plasma clearance of nicotine is lower compared to males [23].…”
Section: Discussionsupporting
confidence: 70%
“…When it comes to gender study, Travis et al observed the susceptibility of lung cancer in female smokers because of tar exposure compared to male counterparts [21]. Similarly, our study also suggests that female smokers are more prone in developing cognitive decline compared to male smokers which may be due to the fast rate of nicotine metabolism by the female hormones and its effect on the cognitive decline [22]. Additionally, females exhibited a higher amount of nicotine intake and the total plasma clearance of nicotine is lower compared to males [23].…”
Section: Discussionsupporting
confidence: 70%
“…However, it is still worth considering potential sex differences as a foundation for future studies. For instance, compared to male rats, nicotine's rewarding effects are enhanced in females in the conditioned place preference paradigm 55 , females acquire intravenous nicotine selfadministration quicker at a low nicotine dose 56 , females demonstrate higher elasticity in demand for nicotine in a behavioral economics assessment 57 , and females exhibit higher motivation to obtain nicotine infusions with the progressive ratio schedule or under extended access conditions (23 hr) 56,58 . Age-related effects have also been found in the reinforcing effects of nicotine on brain reward thresholds, with adolescent females exhibiting a higher sensitivity to nicotine compared to males 59 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that midbrain DA neurons in females are less sensitive to laser stimulation. It is well documented that female rats acquired cocaine (heroin or nicotine) self‐administration more rapidly than males and consumed significantly greater amounts of cocaine, heroin, or nicotine than did males under the same experimental conditions 62–64 . The neural mechanisms underlying sex differences in drug intake are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The neural mechanisms underlying sex differences in drug intake are not fully understood. A prevailing hypothesis is that estrogen effects on the mesolimbic DA systems may underlie such sex differences in drug‐taking behavior 64–66 . Accordingly, such an estrogen‐related mechanism may also explain why females respond less for VTA DA neuron stimulation.…”
Section: Discussionmentioning
confidence: 99%